Strategi Dakwah Program X-School dalam Meningkatkan Pemahaman Keagamaan - Annisa Rahmasari; Komarudin Shaleh (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Nowadays, there are many fans of South Korean culture in Indonesia, but the problem that often occurs is the lack of awareness of studying religious knowledge, resulting in a lack of understanding of their religion. This made a community called XKwavers take the initiative to create an Islamic learning program called X-School. This research aims to find out how the implementation, da’wah strategy, and results of the X-School program’s da’wah strategy in improving the religious understanding of the X-School 2022 participants. This research uses qualitative research methods of descriptive analysis. Data collection techniques in this research were observation, interview, and documentation. The result of this research is that X-School applies sentimental da’wah strategy, rational da’wah strategy, and sensory da’wah strategy in its activities. X-School also has a significant role in increasing the religious understanding of the X-School 2022 participants. From the result of this research, there are supporting and inhibiting factors of X-School in increasing the religious understanding of the participants. The supporting factors are the X-School's da'wah spirit, many people are interested, and interesting concepts. Meanwhile, the inhibiting factor are the unstable signal and paid programs. Abstrak. Dewasa ini, ada banyak penggemar budaya Korea Selatan di Indonesia, namun permasalahan yang sering terjadi adalah kurangnya kesadaran mempelajari ilmu agama sehingga mengakibatkan kurangnya pemahaman keagamaan mereka. Hal ini membuat komunitas bernama XKwavers berinisiatif untuk membuat program belajar agama Islam yang diberi nama X-School. Penelitian ini bertujuan untuk mengetahui bagaimana pelaksanaan, strategi dakwah, serta hasil strategi dakwah program X-School dalam meningkatkan pemahaman keagamaan para peserta X-School 2022. Penelitian ini menggunakan metode penelitian kualitatif analisis deskriptif. Teknik pengumpulan data pada penelitian ini adalah observasi, wawancara, serta dokumentasi. Hasil dari penelitian ini yaitu X-School menerapkan strategi dakwah sentimental, strategi dakwah rasional, dan strategi dakwah indrawi dalam kegiatannya. X-School pun memiliki peran yang cukup signifikan dalam meningkatkan pemahaman keagamaan para peserta X-School 2022. Dari hasil penelitian ini ada faktor pendukung dan penghambat X-School dalam meningkatkan pemahaman keagamaan para peserta. Faktor pendukungnya yaitu semangat berdakwah, banyaknya peminat, dan konsep yang menarik. Sementara faktor penghambatnya adalah kurang stabilnya sinyal dan program yang berbayar.